PERSEPSI ALUMNI DAN STAKEHOLDER POLITEKNIK KESEHATAN SEMARANG TERHADAP KESESUAIAN KEMAMPUAN BAHASA INGGRIS SEBAGAI BEKAL MENGHADAPI KEBUTUHAN DUNIA KERJA - Salikun ,; Supriyana ,; Hermien Nugraheni (Jurnal Kesehatan Gigi, 2014)
ABSTRACT       An English proviciency testl to to measure a person's level of competence in the field of English language should be appropriate to the needs of graduates in the workforce. Meanwhile Indonesia stigma most people still assume that the English language proficiency test is toefl, and less familiar with the other forms of test. In fact, every standardized test functions and has different characteristics. It became the basis of researchers to carry out a study of the English language proficiency test that is appropriate for vocational education as Kemenkes Polytechnic Semarang. For that study. The purpose of this study was to determine the suitability of English proficiency MoH Semarang Health Polytechnic students who have been certified using a test that has been applied in the current stakeholder needs.This research is a descriptive study with a qualitative approach. Subjects in this study were polytechnic graduates Kemenkes Semarang and its stakeholders. Collecting data using two instruments, namely a questionnaire and interviews or in- depth interviews. Questionnaire data were analyzed using the criteria according heaton (1975:172). The data from in- depth interviews described in accordance with the subject 's perception of research.The study results of this showed that the debriefing English language skills during the lectures can be said to be an improvement to be used when entering the workforce. Therefore debriefing skills required more intensive form of English proficiency for students of polytechnic Kemenkes Semarang. It is also necessary to reform the system of standardization the English language to fit the needs of alumni in the world of work. Keywords : graduation, stakeholders, TOEIC, the world of work